2015
DOI: 10.1021/bi501205e
|View full text |Cite
|
Sign up to set email alerts
|

[FeFe]-Hydrogenase Maturation: Insights into the Role HydE Plays in Dithiomethylamine Biosynthesis

Abstract: HydE and HydG are radical S-adenosylmethionine enzymes required for the maturation of [FeFe]-hydrogenase (HydA) and produce the non-protein organic ligands characteristic of its unique catalytic cluster. The catalytic cluster of HydA (the H-cluster) is a typical [4Fe-4S] cubane bridged to a 2Fe-subcluster that contains two carbon monoxide, three cyanide, and a bridging dithiomethylamine as ligands. While recent studies have shed light on the nature of diatomic ligand biosynthesis by HydG, little information ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 72 publications
2
92
0
Order By: Relevance
“…Whereas the [4Fe-4S] H subcluster is inserted by the housekeeping Fe-S cluster machinery, the [2Fe] H subcluster is synthesized and inserted by three accessory proteins: the HydE, HydF, and HydG maturases (5,(7)(8)(9). Both L-tyrosine (Tyr) and L-cysteine (Cys) have been shown to stimulate in vitro [2Fe] H subcluster biosynthesis (10,11) with Tyr serving as the precursor to the CO and CN -ligands (12)(13)(14); the role of Cys in H-cluster maturation is less clear and an emerging area of focus (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the [4Fe-4S] H subcluster is inserted by the housekeeping Fe-S cluster machinery, the [2Fe] H subcluster is synthesized and inserted by three accessory proteins: the HydE, HydF, and HydG maturases (5,(7)(8)(9). Both L-tyrosine (Tyr) and L-cysteine (Cys) have been shown to stimulate in vitro [2Fe] H subcluster biosynthesis (10,11) with Tyr serving as the precursor to the CO and CN -ligands (12)(13)(14); the role of Cys in H-cluster maturation is less clear and an emerging area of focus (15).…”
mentioning
confidence: 99%
“…1B). The substrate and product of the radical SAM enzyme HydE are presently unknown, although it is thought that HydE plays a role in building the azadithiolate ligand (5,15). HydG and HydE are thought to function in concert with the GTP-hydrolyzing enzyme HydF (18,19) to generate a [2Fe] H subcluster-like precursor (20)(21)(22) that is transferred to the hydrogenase apoprotein (apo-HydA) to yield the mature H cluster.…”
mentioning
confidence: 99%
“…Work from several laboratories has shown that the maturation of the [FeFe] center requires at least three protein maturases: HydF that has GTPase activity and appears to be both a [FeFe] center scaffold and carrier (8,9), HydG that synthesizes CO and CN − from tyrosine (10)(11)(12)(13), and HydE that, by elimination, should be involved in the synthesis of the DTMA bridge (14,15). Both HydE and HydG are members of the large radical S-adenosyl-L-methionine (SAM) protein family (16,17).…”
mentioning
confidence: 99%
“…The structure of HydE (Figure 4a) includes a large cavity (991 Å 3 ) within the TIM barrel that is well suited to bind a second substrate (in addition to SAM). Efforts to identify this substrate include in silico [24] and in vitro screening experiments [32,33]. The rate of SAM turnover to form 5ʹ-deoxyadenosine was recently used to screen a range of putative HydE second substrates, leading to the conclusion that the HydE substrate likely contains a thiol [33].…”
Section: Hyde: 'A Riddle Wrapped In a Mystery Inside An Enigma'mentioning
confidence: 99%
“…Efforts to identify this substrate include in silico [24] and in vitro screening experiments [32,33]. The rate of SAM turnover to form 5ʹ-deoxyadenosine was recently used to screen a range of putative HydE second substrates, leading to the conclusion that the HydE substrate likely contains a thiol [33]. Thiocyanate was identified as a fragment with significant affinity for HydE [30] and more recent studies with HydE crystals demonstrated that a small molecule, (2R,4R)-2-methyl-1,3-thiazolidine-2,4-dicarboxylic acid, could intercept the 5ʹ-deoxyadenosyl radical intermediate, forming a new 5ʹ-C to sulfur bond in the product [32].…”
Section: Hyde: 'A Riddle Wrapped In a Mystery Inside An Enigma'mentioning
confidence: 99%